ANALYSIS OF INTERNATIONAL EXPERIENCE IN THE DEVELOPMENT AND USE OF MODELS OF DIGITAL TRANSFORMATION OF HIGHER EDUCATION ORGANIZATIONS - Akhmetov Б.С.; Karlov И.А.; Zhilkishbayev А.А.; Serikbayev Т.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article presents an analysis of five international and national framework models for digital transformation of higher education organizations, identifies priority areas of university transformation in the context of an evolving digital environment, identifies typical deficiencies found in national programs and strategies for digital transformation of higher education organizations. The article is aimed at identifying the main directions of changes in the activities of educational organizations provided for in these frameworks, as well as correlating them with the activities provided for in national programs and strategies for digital transformation of higher education organizations and identifying systemic deficits. The article describes the digital strategies of individual universities, which are developed in accordance with the goals and objectives of a particular university, its competencies and deficits, as well as the expectations of its main stakeholders.